O Encontro Cultural de Laranjeiras e o protagonismo intelectual de Beatriz Góis Dantas (1972-2023) - Santos, Ingrid Batista (2023)
The present study aims to analyze the contributions of anthropologist Beatriz Góis Dantas at the Laranjeiras Cultural Meeting Symposium. Whether through the analysis of academic training and professional performance, or through the areas of research she covered, notably how she became interested in the city of Laranjeiras-SE and how she began her studies on various topics belonging to that location. Laranjeiras, since 1968, has become a common part of Dantas’ activities. In addition to a vast popular culture, the municipality has held the Laranjeiras Cultural Meeting annually since 1976. It is the longest-running and uninterrupted event on folklore and popular culture in the country. The researcher contributed from its elaboration to its implementation and, during the forty-eight editions, she participated several times, presenting some result of the countless researches she developed or as a debater in some communication, or even, producing books, articles, sources regarding the event. When talking about this event, the name of the anthropologist is soon mentioned, associating her with this space that she used to produce and share knowledge.